Combination therapy protects macaques against advanced Marburg virus disease - Robert W. Cross (Nature Portfolio, 2021)
Extending the therapeutic window for acute viral infections could save lives. Here, the authors show that combination treatment with a human monoclonal antibody and remdesivir initiated at 6 days post infection with Marburg virus provides 80% protection in non-human primates.